Dynamics of Social Media Interaction: Implications for the Manifestation of Digital Business Image and Reputation in Public Perception - Amrozi, Akhmad Imam; Ghofur, Abdul; Damayanti, Dhita Dhora; Suprapto, Hery; Sulaeman, Moh Muklis (Technology and Society Perspectives (TACIT), 2024)
In recent years, social media has experienced rapid growth as the primary platform for interaction, information sharing, and community building. This phenomenon has transformed the communication landscape and influenced how companies interact with consumers. This research aims to deeply understand and contextualize the dynamics of social media interaction, implications for the manifestation of image, and digital business reputation in public perception. The research method employed is a qualitative literature review using data from Google Scholar for the period 1998-2023. The study results indicate that the dynamics of social media interaction have become crucial in the digital era, particularly in shaping the image and reputation of digital businesses in the eyes of the public. These interactions include responses to content, user interactions, as well as the role of influencers and communities in shaping public opinion. The image and reputation of digital businesses are formed through various mechanisms on social media, including user reviews, recommendations, and content dissemination by other users.